P5_1 Squashing Slitheen - Evershed, Mabel Elisabeth; Baldwin, Emily Jane; Beedle, Thomas James; Cook, Naomi Esther (Physics Special Topics, 2017)
To disguise themselves on Earth, Raxacoricofallapatorians hid in suits of human skin using a compression field worn around their necks. Over time, developments in their technology allowed them to fit into average sized humans, as opposed to obese humans used previously. We calculated the pressure exerted on the inside of the skin as 75,000 Pa for an average human and 64,300 Pa for an obese human, both significantly beneath the ultimate tensile strength of human skin. We calculated the force from the compression fields to be 272,000 N and 233,000 N for average and obese humans respectively.